Analisis Prediksi Kebangkrutan Menggunakan Metode Altman Z-Score Pada PT. Dua Sahabat Sejati Borneo - Anissa Nuor Octavia - (KINDAI, 2023)
The aim of this research is to analyze bankruptcy prediction using the Altman Z-Score method at PT. DSSB for the 2019-2021 period. This type of research is descriptive quantitative. Using secondary data with the research population of the financial statements of PT. DSSB period 2019–2021. The research sample is the balance sheet financial statements and profit/loss reports for the 2019–2021 period. Data analysis used analysis of financial performance ratios and bankruptcy prediction analysis Altman Z-Score (Modified Altman). The results show that from the calculation of financial performance, the liquidity ratio is below the industry standard due to an increase in trade payables in each period. The activity ratio on the company's total turnover ratio can maximize the use of assets, the working capital turnover ratio shows a negative number because the working capital owned is not enough to finance sales activities. The profitability ratio is below the industry standard due to the high cost of goods sold and high general administrative costs, as well as other expenses. In calculating the Z-Score analysis, it is always in a dangerous zone, which is a condition where a company experiences financial difficulties with high risk. Keywords: Financial Performance, Bankruptcy Prediction, Altman Z-Score